PELAKSANAAN PEMBELAJARAN IPS BERBASIS KEUNGGULAN LOKAL DALAM UPAYA MEMBANGUN KETERAMPILAN SOSIAL MAHASISWA PENDIDIKAN IPS - Aisyah Nur Sayyidatun Nisa (Universitas Muria Kudus, 2016)
This research is an Sosial Studies-based learning local excellence. Through learning thelocal excellence, specific goals to be achieved are expected sosial intelligence of students will bebetter and make positive contribution to students of Sosial Studies education in terms of gaining asunderstanding, monitor learning, interaction, participation and to develop new relationships.This is a qualitative research, with a case study design, the subject is a students andlecturer of Sosial Studies Education Departement, Sosial Sciences Faculty, Semarang University.This analysis using qualitative analysis, with interactive analysis, presented data with tabular fromand the interpretation, in order to obtain the appropriate conclusions. Learning implementationwent smootly, got a very good response, can explore social skill of the students, learning inside andoutside of learning.